HUBUNGAN INISIASI MENYUSUI DINI DENGAN KEBERHASILAN PEMBERIAN ASI EKSLUSIF PADA MASA NEONATUS DI UPTD PUSKESMAS KUALA SEMPANG - Siregar, Imawati; Sihombing, Sarmauli Franshisca (Universitas Batam, 2020)
Early initiation of breastfeeding is very important because it is one of the supporters for the success of exclusive breastfeeding in neonates. WHO recommends exclusive breastfeeding for the first 6 months of life and continued with complementary foods until the age of 2 years. A total of 136.7 million newborns worldwide and only 32.6% of them are exclusively breastfed in the first 6 months, while in developing countries only 39% of mothers are exclusively breastfed. The success of exclusive breastfeeding begins with the optimal implementation of the IMD process. The purpose of this study was to determine whether there was a relationship between Early Initiation of Breastfeeding and the success of exclusive breastfeeding during the neonatal period in the UPTD area of the Kuala Sempang Health Center. This study used a quantitative descriptive design and was conducted at the UPTD Puskesmas Kuala Sempang. The population of this study is mothers who have babies aged 7-12 months with a sample of 70 respondents. Based on the results of this study, it is known that there are 57 respondents (81.4%) who carry out Early Breastfeeding Initiation from 70 respondents, while 29 respondents (41.4%). The results of statistical tests to see the relationship between the two variables using the chi square test obtained a p value of 0.035. This shows that the conclusion of this study is that there is a relationship between early breastfeeding initiation and the success of exclusive breastfeeding in the Uptd area of Kuala Sempang Health Center. Suggestions to be able to carry out Early Initiation of Breastfeeding well and to be able to provide exclusive breastfeeding.